The Skyscape of Mount Murad, Armenia: A Possible Pastoral Calendar and Ritual Site. (23rd April 2019) - Frincu, Marc
Abstract : This article presents a complex site located at Mount Murad in Armenia, examining its possible astronomical significance in relation to summer pastoral activities. The site consists of a necropolis containing tumuli and recent graves, as well as a significant concentration of rock art, sheepfolds and an interesting circular enclosure with two strands of stone, three cairns and a stone arc attached to it. Facial features were identified on a carved rock in the circle, suggestive of ritual use. Much of Armenia's rich archaeological heritage is located high in the mountains and has not yet been properly investigated from an archaeological or archaeoastronomical perspective, and what literature there is on archaeoastronomy focuses on Qarahunj and rock art. This study aims to raise awareness of the significance of the Mount Murad site, which deserves proper archaeological investigation to determine the date and purpose of its numerous structures.